Pengaruh Pupuk Hayati Hormax dan Jarak Tanam terhadap Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis hypogaea L.) Varietas Garuda Biga - Rohendi, Tatang; Komariah, Ai; Parlinah, Linlin (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
The research was conducted in Dawuan Kidul Village, Dawuan District, Subang Regency with an altitude of 700 m above sea level, with a type B (wet) climate from September 2022 to December 2022. This study aims to: (1) determine the effect of the interaction between the concentrations of the hormax biofertilizer and spacing on the growth and yield of peanut (Arachis hypogaea L.) variety Biga, (2) knowing the concentration of hormax biofertilizer and spacing that gives the best results on peanut (Arachis hypogaea L.) variety Biga. The experimental design used was a split plot design with a factorial pattern with Duncan's follow-up test. Hormax concentration treatment (k) consisted of 4 levels, namely k0 (concentration 0 ml/L solution), k2 (concentration 5 ml/L solution), k3 (concentration 10 ml/L solution), k4 (concentration 15 ml/L solution) . The spacing treatment (j) consisted of 4 levels, namely j1 (30x15 cm), j2 (30x20 cm), j3 (30x25 cm), j4 (30x30 cm). The results showed that there was an interaction between the concentration of hormax biofertilizer and plant spacing on the response of plant height 21 HST, number of leaves 21 HST, 35 HST, 49 HST and the number of pods planted. The best interaction was shown from the application of 5 and 10 ml/L biological fertilizer solution at a spacing of 30x30cm for a plant height response of 21 DAP, the provision of 15 ml/L biological fertilizer solution at a spacing of 30x25cm was best for a response of 21 DAP leaves, the application of 15 ml biological fertilizer /L solution at a spacing of 30x20 was the best for the response to the number of leaves of 35 HST and the application of biological fertilizer 5 ml/L solution at a spacing of 30x20 was best for the response to the number of leaves of 49 HST and the number of pods.